Pharmacological screening of Alsotonia scholaris - Rathor, Vinod; Wadhwa, Shailendra; Deb, Jyotirmoy; Choudhury, Ananta (Journal of Applied Pharmaceutical Research, 2015)
A large number of medicinal plants are claimed to possess anthelmintic property in traditional systems of medicine and are also utilize by ethnic groups worldwide. The development of anthelmintic resistance and the high cost of conventional anthelmintic drugs led to the evaluation of medicinal plant as an alternative source of anthelmintice. In the current study were conducted to determine the possible anthelmintic and antibacterial effects of leaves of Alstonia scholaris. The plant Alstonia scholaris has been used in different system of traditional medication for the treatment of diseases and ailments of human beings including anthelmintic activity.